Effects of reclamation and natural changes on coastal wetlands bordering China's Yellow Sea from 1984 to 2015. (4th July 2019) - Chen, Ying; Dong, Jinwei; Xiao, Xiangming; Ma, Zhijun; Tan, Kun; Melville, David; Li, Bo; Lu, Haiying; Liu, Jinfu; Liu, Fengshan
Abstract: Coastal wetlands are rapidly disappearing worldwide, which is posing a substantial threat to the integrity of coastal ecosystems. In addition to the direct area reduction caused by reclamation, coastal wetlands experience natural changes due to sediment transport in coastal regions. Arguably, the reclamation rates must be less than the net accretion rate to guarantee the restoration of coastal wetlands. By applying an automatic and replicable shoreline algorithm to all available Landsat imagery from 1984 to 2015 using the Google Earth Engine Cloud Platform, we developed distribution maps of coastal wetlands and reclamation in China's Yellow Sea (CYS) at 4‐ or 5‐year intervals. In addition, we divided coastal wetlands into saltmarshes and mudflats and analysed their trends separately. Over the past 30 years, the area of coastal wetlands decreased by 53% (from 6, 463 to 3, 036 km 2 ), including a 67% decrease in saltmarshes (from 1, 471 to 489 km 2 ) and a 49% decrease in mudflats (from 4, 992 to 2, 547 km 2 ). Meanwhile, the reclaimed area was 7, 696 km 2 (including 1, 276 km 2 of saltmarshes and 3, 002 km 2 of mudflats), which exceeded the area of newly formed coastal wetlands (852 km 2 ). The natural state of mudflats gradually changed from accretion to erosion, but without considering the natural state of coastal wetlands, reclamation will continue at a high rate in CYS according to China's national marine functional zoning (MFZ) for 2010–2020. In view of their important ecological services, there is an urgent need to revise the national MFZ to achieve 'no net loss' of coastal wetlands.